The Impact of Treatment on the Public Safety Outcomes of Mental Health Court Participants. (February 2013) - Keator, Karli J.; Callahan, Lisa; Steadman, Henry J.; Vesselinov, Roumen
Three mental health courts (MHCs) are included in this study of whether enrollment in MHC affects community treatment access, utilization, time to service, program outcome, arrests, and jail days. Researchers approached newly enrolled MHC participants ( n = 296) and similar "treatment as usual" (TAU) jail detainees ( n = 386) screened as eligible for study participation. Baseline and 6-month interviews were conducted, and respondents allowed researchers access to their mental health and criminal justice records. We found that on discharge from jail on target charges, MHC participants accessed community treatment more quickly than did the TAU respondents. Furthermore, prior to enrollment in MHC, this sample had twice as many crisis treatment episodes as the TAUs, and they received more therapeutic treatment episodes. One year after enrollment, the MHC sample had more intensive and therapeutic treatment episodes than the TAUs. We found no relationship between the type of treatment intervention received (or not) and whether the MHC enrollees were arrested or in jail following MHC enrollment.